Cinco canções de Maria Helena Buzelin (1931-2005): resgate histórico por meio de edição de perfomance, análise estilística e dados biográficos - Urbano Francisco Peres de Lima (2019)
The subject of this dissertation was the Brazilian women composer Maria Helena Buzelin´s (1931 – 2005) life and work. Up to this moment, the task of cataloging her work was successful in finding five songs for singing and piano, all of them composed from her spouse's poems - Dalnio Teixeira Starling (1926 - 2016). There are numerous data available on this artist's career, who was considerably active from the 50s to the 80s of the 20th century and who was outstanding as a soloist soprano in national and international performances. Therefore, the finding of this small collection, examined in this dissertation, will become a relevant data that will contribute in mapping Brazilian songs, putting them together and making available more titles of our chamber music production.